1997
DOI: 10.1007/s004250050106
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid signal transduction in epidermal cells of Pisum sativum L. Argenteum : both dehydrin mRNA accumulation and stomatal responses require protein phosphorylation and dephosphorylation

Abstract: The eects of a number of treatments, both in planta and in vitro, on the accumulation of mRNA encoding dehydrin, an abscisic acid (ABA)-inducible protein, were determined for guard cells and mesophyll cells prepared from leaves of the Argenteum mutant of Pisum sativum L. Guard cells and mesophyll cells treated for 10 d with ABA in planta accumulated dehydrin mRNA. However, after 1 or 3 d treatment, dehydrin mRNA was induced only in guard cells. Wilting induced dehydrin mRNA accumulation in leaves and epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…6 and 7). It is interesting that Ppc1 expression was found to be enhanced by treating detached leaves with CsA or ascomycin, although this was probably an indirect effect due to excessive fresh weight loss from the leaves, since CsA is known to antagonize ABA-inhibited stomatal opening and ABA-induced stomatal closure (Hey et al, 1997). However, ascomycin treatment did not lead to an increase in fresh weight loss in dehydration and ABA-treated leaves, suggesting that Ppc1 transcript accumulation may be a direct effect of this PP2B inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…6 and 7). It is interesting that Ppc1 expression was found to be enhanced by treating detached leaves with CsA or ascomycin, although this was probably an indirect effect due to excessive fresh weight loss from the leaves, since CsA is known to antagonize ABA-inhibited stomatal opening and ABA-induced stomatal closure (Hey et al, 1997). However, ascomycin treatment did not lead to an increase in fresh weight loss in dehydration and ABA-treated leaves, suggesting that Ppc1 transcript accumulation may be a direct effect of this PP2B inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the catalytic subunit mutant pp2ac2 exhibited ABA hypersensitivity in seed germination, root growth, and seedling development (Pernas et al, 2007). Previous pharmacological studies have suggested that both positively regulating and negatively regulating PP2A-type protein phosphatases function in ABA signaling (Schmidt et al, 1995;Hey et al, 1997), leading to the question of the identity of the underlying genes.…”
mentioning
confidence: 96%
“…Previous studies on stomatal ABA responses using the PP2A-type protein phosphatase inhibitor okadaic acid provided evidence that okadaic acid-sensitive protein phosphatases function as negative regulators of ABA responses in Pisum sativum and V. faba (Schmidt et al, 1995;Hey et al, 1997;Schwarz and Schroeder, 1998) and as positive regulators in Arabidopsis (Pei et al, 1997;Kwak et al, 2002). Moreover, research in P. sativum suggested that okadaic acidsensitive protein phosphatases function as negative and positive regulators of ABA responses depending on the conditions (Hey et al, 1997). PP2A-type protein phosphatases function not only in ABA responses but also, in other plant hormone and light responses (Lillo et al, 2014).…”
Section: Pp2a-type Protein Phosphatases Function In Aba Responsesmentioning
confidence: 99%
“…The raw data were analyzed by model selection using Generalized Linear modeling with a Gamma response and inverse link, and the calculated apertures and error bars are shown. Hey et al, 1997) were then homogenized in TRIzol reagent (1 mL) with glass beads in a Fastprep bead beater (Fisher, Loughborough, UK) to break open the guard cells. RNA was extracted following the TRIzol RNA extraction procedure provided by the manufacturers.…”
mentioning
confidence: 99%